The Effects of Unemployment Compensation in General Equilibrium with Search Unemployment - Bo Axell; Harald Lang (The Research Institute of Industrial Economics (IUI), 1986)
In this article it is shown that when the effects of an increase in unemployment subsidies are studied in a general equilibrium framework, unemployment increases far less than in a 'partial-partial' model, or may even decrease.
Keywords: J64; J65; 330; Unemployment subsidies; general equilibrium; partial model